PENTOSAN POLYSULPHATE INFLUENCEON THE COURSE OF CHRONICKIDNEYDISEASE ST’. II - IV - Dudari, O.; Shifrisi, M.; Driyanska, V.Ye.; Krot, V.F.; Loboda, O.M.; Krasiuke, K.; Krylova, M.H.; N.G., Alexeeva; Bryzhachenko, T.P. (Ukrainian Journal of Nephrology and Dialysis, 2015)
The aim is to determine the effect of the drug pentosan polysulphate at the rate of disease progression in patients with CKD II - IVst., to confirmation of lipid - lowering action and setting of the drug on indicators of chronic inflammation. Materials and methods. Tests conducted in one center for 12 weeks. The study included 60patients with CKD II - IV st. Patients were divided into 2 groups: group 1 (basic) - 30patients in addition to standard therapy receiving study medication, pentosan polysulphate, group 2 - 30 patients received only standard therapy. The drug pentosan polysulphate was administered for 8 - weeks: 100 mg. a day intramuscularly or intravenously for 3 weeks, followed by oral administration of 50 mg two times a day. The survey studied the dynamics ofdaily proteinuria, GFR, lipids, indicators of tumor necrosis factor, IL - 18 and vascular endothelial growth factor (VEGF) before and after treatment (12 week observation). Results. It was found a significant decrease in total cholesterol and atherogenic ratio after 3 months of treatment in the study group, hypolipidemic effect is more significant than in the comparison group. The group used pentosan polysulphate proteinuria reduction was more pronounced, and was 65% against 38% in the comparison group. Pentosan polysulphate in the treatment ofCKDpatients in stages II - IV contributes to significant decrease in inflammatory cytokines (IL - 18 and TNF - a) in contrast to the comparison group. Conclusions. The use of pentosan polysulphate in the treatment of patients with CKD stages II - IV had positive effect on lipid metabolism. Purpose pentosan polysulphate patients with CKD stages II - IV contributes to a significant reduction of the daily proteinuria and eGFR improvement, reduces levels of inflammatory cytokines: IL - 18 and TNF - a.